Embodied frictional artistic encounters: The use of creativity and embodied learning as transformativeand healing space/s - Lewis, Janine (Critical Studies in Teaching and Learning, 2025)
Offered as conversations with Elmarie Costandius as reflection on practice, this article discusses the use of creative learning processes as transformative and healing space/s, and further proposes that these activation spaces be named embodied frictional artistic encounters. The construct of embodied frictional artistic encounters includes three vital participants, the artist (as creative act) as the facilitator of the immersive experience together with the spect-actor, within a designated intra-active environment. Collectively these participants collaborate to activate the artistic encounters towards a transformative and healing outcome. These communal shared intra-active space/s are heightened through affect, resonance, and wit(h)nessing, where the frictional element pertains to awakening states of doubt to alter perspective forming towards empathy. This article intends to encapsulate creative embodied learning within embodied frictional artistic encounters (celFAE/CELfae) and offer this as a dynamic means to classify such activations that serve to foster change and healing.